Influence of Hinterland Bedrock Lithologies on Aspect of Borneo's Deepwater Fold and Thrust Belt - Andrew Cullen (Berita Sedimentologi, 2011)
Each of the catchment areas of Borneo’s major river systems has distinct differences in their bedrock lithologies. As the provenance for the sediments delivered to the deepwater depositional systems, these lithological variations in the hinterland are an important consideration when predicting high quality turbidite reservoirs as they influence compaction and diagenesis. This paper examines these issues for the Baram, Sandakan, Tarakan, and Kutei Basins. Additionally, the role of hinterland bedrock composition of the Baram and Padas Rivers is considered in terms of influencing along strike changes in the structural style of the Northwest Borneo deepwater fold and thrust belts.